OS IMPACTOS E CONSEQUÊNCIAS DA ROTATIVIDADE DE PESSOAL SOBRE A MEMÓRIA ORGANIZACIONAL: UM ESTUDO NO COMÉRCIO VAREJISTA - Jubilato, Jorge (2008)
This research is to understand the impact of the organizational memory in organizations which have a high index of employee turnover. With a economy based on knowledge, a new worker appears, called for Peter Drucker (1993) as "worker of knowledge". In this new economy, the organizations face uncertainties and intense competition environments, where the new intangible assets, the knowledge, become the key to obtain competitive advantage, making them able to gain new market share and increasing its profitability. However, in these competitive environments, the evasion of employees is becoming more frequent, even because they are searching for better placements, or because the organizations pass thrue reengeneering processes, that could impact in employee reduction, or because they have obsolete knowledge. Beyond the exposed, thrue exploratory survey in retail organizations, were investigated different ways to store employee knowledge even if he leaves the company, retaining the knowledge and identifying the main impacts in processes quality and productivity. In this survey we will also present some actions to organizations contribuite to increase employee satisfaction and create the proud of belonging. The main goal of this actions is to retain employees and their knowledge, the most valueble organization patrimony.(AU)